The Paradigm of Salaf Pesantren: The Concept of Charismatic Spiritual Leadership of Kyai at Assalafiyah Pesantren - Sari Hernawati; Khoirun Nofik; Hafizh, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines the charismatic spiritual leadership model of Kyai Subhan Makmun at Pondok Pesantren Assalafiyah. This focus is based on the limited in-depth studies on the influence of charismatic spiritual leadership within the context of traditional Islamic boarding schools (pesantren salaf). Previous research has predominantly concentrated on general leadership models in pesantren, leaving a gap in understanding how charismatic spiritual leadership impacts educational policies and development strategies in these institutions. The aim of this research is to identify and analyze how Kyai Subhan's leadership style influences educational policies and development strategies at Pesantren Assalafiyah and its impact on the quality of education provided. The research employs a qualitative descriptive approach, with data collection through observation, interviews, and documentation. The data is analyzed qualitatively using triangulation to enhance the validity of the findings. The results indicate that Kyai Subhan's charismatic spiritual leadership has a significant positive impact on the educational policies and service strategies at the institution. Through principles of piety and simplicity, Kyai Subhan serves as a role model for students and the surrounding community. His charismatic leadership is manifested in his exceptional ability to mobilize the pesantren community, carry out the mission of the traditional educational institution, and realize the vision of Pondok Pesantren Assalafiyah. The crucial role of the Kyai in the sustainability of the pesantren underscores the strategic position of the Kyai as a leader.